2023
DOI: 10.3389/fdmed.2022.1010916
|View full text |Cite
|
Sign up to set email alerts
|

Laser-activated irrigation: Cavitation and streaming effects from dental lasers

Abstract: IntroductionThe aim of the present study was to assess the generation of laser-activated irrigation (LAI) with a 9,300-nm CO2 laser, a 455- and 970-nm diode laser as well as an 810- and 980-nm diode laser with and without carbon-coated “hot-tips” for improved irrigation in endodontics. Therefore, the formation of cavitation bubbles at the laser tip-ends in different liquids was evaluated and compared to the traditionally applied Er:YAG laser.MethodsThe CO2 laser was applied at different power settings at a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Er:YAG and CO 2 lasers were activated within the pulpal chamber. Both lasers are very well-absorbed by water-based irrigants and introduce relatively large vapor bubbles and high streaming velocities [19]. Other investigations showed that the temperature increase of the irrigant after 20 s of activation within the coronal part of an artificial plastic root model ranged between 7°C with the Er:YAG and 15°C with the CO 2 laser with 0.4 W power input [20].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Er:YAG and CO 2 lasers were activated within the pulpal chamber. Both lasers are very well-absorbed by water-based irrigants and introduce relatively large vapor bubbles and high streaming velocities [19]. Other investigations showed that the temperature increase of the irrigant after 20 s of activation within the coronal part of an artificial plastic root model ranged between 7°C with the Er:YAG and 15°C with the CO 2 laser with 0.4 W power input [20].…”
Section: Discussionmentioning
confidence: 99%
“…Er:YAG (Light Touch, Light Instruments Ltd, Yokneam, Israel) and CO 2 laser (Solea, Convergent dental, Waltham, MA, USA) tips were activated at the root canal entrance while the tips of diode laser SIROLASE (Sirona dental systems GmbH, Bensheim, Germany) and diode laser WISER (Lambda SpA, Brendola, Italy) were inserted up to the working length minus 2 mm and moved in coronal to apical direction in continuous helical movements at 1 mm/s (see Figure 1). Diode laser tips were coated black prior to use with carbon particles (Carbon black, acetylene 100%, compressed, 99.9+%, Alfa Aesar, Kandel, Germany) that were glued with a transparent glue-spray (Toolcraft, Conrad Electronic AG, Wollerau, Switzerland) [19]. During activation, the liquid level in the access cavity was constantly controlled and replenished when needed.…”
Section: Shaping and Cleaningmentioning
confidence: 99%
See 3 more Smart Citations